The cultural other, interculture and interculturality in postcolonial translation dialogic-communication
This article takes its point of departure from the Sapir-Whorf hypothesis to heuristically establish the nature of cultural otherness, interculture and interculturality in postcolonial translation communication. It posits that postcolonial translation communication takes a discursive-dialogic form that implicates the conflicts and asymmetry of cultural relations between ex-coloniser and excolonised cultures and societies. The excoloniser and excolonised are respectively on the quest for continuing dominance and self-liberation. Illustrating with text units from German translated Things Fall Apart, the paper concludes on the relevance of postcolonial translation critics to enhance positive outcomes in postcolonial textual communicative relations particularly between Africa and Europe.